(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The term "honorifics" refers to certain grammatical constructions utilized as nods of respect to the addressee. The researchers find a flaw in this definition since it requires honorifics to be sent solely to an addressee, which is inconsistent with the types that will be made clearer later. This article describes theoretical analysis of the term honorifics in English.